The Stone Age of Qeqertarsuup Tunua (Disko Bugt) (Vol. 336):A regional analysis of the Saqqaq and Dorset cultures of Central West Greenland - Jensen, Jens Fog (Museum Tusculanum Press, 2006)
suup Tunua, however the archaeological evidence for such a development has yet to be found. When the cultural history of Qeqertarsuup Tunua is compared with that of Peary Land, the dwelling types and chronological units appear very similar. In the case of Dorset and Independence II, the similarities also extend to include the lithic inventory. As a consequence it is difficult to maintain a division between Dorset in Western and Southern Greenland and Independence II in the High Arctic.